Leczenie chirurgiczne głębokich oparzeń chemicznych powiek - Żurada, Agnieszka; Zieliński, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Chemical burns of the eyelids are common, and this may lead to ocular damage. A direct insult of the eyes that result in permanent damage, is rare in facial burns. The majority of the chemical burns of eyelids are partialthickness that heal spontaneously in 1 week. Whereas, 10 percent are full-thickness burns that require release of contractures and grafts. Wound contracture can cause ectropion of the eyelid, resulting in exposure keratitis, conjunctivitis, corneal ulcers, perforation, and even blindness. At our departments, thirteen patients with 28 chemical burns of eyelids of third-degree, were reviewed. The eyelids had burns wounds with granulation and necrotic tissue. All patients had severe cicatrical ectropion. The eyelids were released with incisions running along the eyelid margin, down to the orbicularis muscle, including the distal part of the levator palpebrae superioris muscle, when necessary. To cover the resulting defects, we use generous full-thickness skin grafts, if available, for both the upper and lower eyelids. Rarely has a tarsorrhaphy been required, and properly constructed dressing provides satisfactory eyelid margin immobilization and conjunctival hygiene. Eighteen full-thickness grafts in 10 patients are reported 8 to12 weeks after grafting. In seven eyelids, 3 patients developed ectropion and required reconstruction of the eyelids. Our series demonstrates that the early grafting of eyelid burns with full-thickness grafts, can prevent the development of recurrent cicatrical ectropion. Split-thickness grafting should be limited to cases where we can not find the hairless donor site for full-thickness skin grafts.